Gene Expression during Imidacloprid-Induced Hormesis in Green Peach Aphid - Murali-Mohan Ayyanath; G. Christopher Cutler; Cynthia D. Scott-Dupree; Balakrishnan Prithiviraj; Saveetha Kandasamy; Kalyani Prithiviraj (SAGE Publishing, 2014)
Imidacloprid-induced hormesis in the form of stimulated reproduction has previously been reported in green peach aphid, Myzus persicae . Changes in gene expression accompanying this hormetic response have not been previously investigated. In this study, expression of stress response (Hsp60) , dispersal ( OSD, TOL and ANT) , and developmental (FPPS I) genes were examined for two generations during imidacloprid-induced reproductive stimulation in M. persicae . Global DNA methylation was also measured to test the hypothesis that changes in gene expression are heritable. At hormetic concentrations, down-regulation of Hsp60 was followed by up-regulation of this gene in the subsequent generation. Likewise, expression of dispersal-related genes and FPPS I varied with concentration, life stage, and generation. These results indicate that reproductive hormesis in M. persicae is accompanied by a complex transgenerational pattern of up- and down-regulation of genes that likely reflects trade-offs in gene expression and related physiological processes during the phenotypic dose-response. Moreover, DNA methylation in second generation M. persicae occurred at higher doses than in first-generation aphids, suggesting that heritable adaptability to low doses of the stressor might have occurred.